2013
DOI: 10.3390/molecules180910497
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Quantitative Structure-Property Relationships of Side Chain-Modified Hyodeoxycholic Acid Derivatives

Abstract: Bile acids have emerged as versatile signalling compounds of a complex network of nuclear and membrane receptors regulating various endocrine and paracrine functions. The elucidation of the interconnection between the biological pathways under the bile acid control and manifestations of hepatic and metabolic diseases have extended the scope of this class of steroids for in vivo investigations. In this framework, the design and synthesis of novel biliary derivatives able to modulate a specific receptor requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Investigations have suggested that lower luminal levels of chenodeoxycholate are associated with decreased gastric emptying times and reduced expression of the pro-inflammatory cytokines TNF-a, IL-1B, IL-6, and IL-8 ( Goyal et al, 2015 ; Peleman et al, 2016 ). The decrease in chenodeoxycholate may be associated with metabolism of hyodeoxycholate a secondary bile acid resulting from bacterial metabolism of chenodeoxycholate ( Sabbatini et al, 2013 ; Theriot et al, 2016 ). In the colonic lumen, rodent studies suggest that hyodeoxycholate acts directly on goblet cells to increase mucus production, thereby modulating barrier function ( Barcelo et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have suggested that lower luminal levels of chenodeoxycholate are associated with decreased gastric emptying times and reduced expression of the pro-inflammatory cytokines TNF-a, IL-1B, IL-6, and IL-8 ( Goyal et al, 2015 ; Peleman et al, 2016 ). The decrease in chenodeoxycholate may be associated with metabolism of hyodeoxycholate a secondary bile acid resulting from bacterial metabolism of chenodeoxycholate ( Sabbatini et al, 2013 ; Theriot et al, 2016 ). In the colonic lumen, rodent studies suggest that hyodeoxycholate acts directly on goblet cells to increase mucus production, thereby modulating barrier function ( Barcelo et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…1, C 24 H 40 O 4 , CASRN: 83-49-8) is also known as 3α,6α-dihydroxy-5β-cholan-24-oic acid or HDCA, which is a secondary bile acid that is one of the metabolic byproducts of intestinal bacteria. It is widely used in treatment of hypertension and coronary artery disease [1,2]. Besides, HDCA was used as an anti-inflammatory drug to treat chronic bronchitis and infantile viral respiratory tract inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The enantioselective dDCC outlined herein can be applied to simplify the synthesis of both medicinally important structures and intermediates employed in natural product total synthesis (Figure ). For instance, the bile-acid derivative 49 (Figure A) was previously prepared from commercial hyodeoxycholic acid 47 as an inseparable mixture of diastereomers at C-24 in 15 steps with only one of those steps making a key C–C bond . In contrast, the same starting material could be enlisted to afford the desired product in only four steps as the major isomer (96:4 dr).…”
mentioning
confidence: 99%
“…A vast array of RAEs derived from readily available alkyl carboxylic acids were tested. Aside from simple alkyl chains (3,5,6,18), a broad range of functional groups could be tolerated, such as terminal alkenes (4), internal alkenes (35, 37, 38), a trifluoromethyl group (8), terminal alkynes (9), internal alkynes (10,36), alkyl halides (15,17), aryl halides (7), ketones (16,41,42), silyl ethers (20), ethers (11,19), imides (14), heterocycles (12,13), lactones (38), carbamates (39, 40), and esters (39, 40). Several RAEs derived from malonate derivatives were also explored ranging from various substitutions on the phenyl ring (21−27) to substrates containing alkyl fluorides (32), nitriles (31), and internal alkenes (33, 34).…”
mentioning
confidence: 99%
See 1 more Smart Citation